Stellaria yabulaiensis (Caryophyllaceae), a new species from Inner Mongolia, China - Lei Liu; Xiao-Jing Qiang; Fan Huang; Xiu-Zheng Huang; Ya-Lin Yu (PhytoKeys)
Stellaria yabulaiensis (Caryophyllaceae), a new species from Inner Mongolia, China, is described and depicted with photographic illustrations. It is similar to S. bistyla, from which differs in its slender fibrous root, longer leaves and pedicel, occurrence of three styles, and more seeds. A morphological comparison among the new species and the similar ones is also provided.